Pendampingan Rebranding Logo Dan Pemanfaatan Digital Marketing Sebagai Solusi Pengembangan UMKM Di Kota Blitar - Bowo Santoso; Delia Noor Rizkita Kisworo (jurnal ABDIMAS Indonesia, 2023)
In the Blitar city there are several MSMEs farming ornamental fish, one of them is Mbah Bendo Koi Farm which is located on Jl. Kapuas No. 92, Kel. Bendo, Kec. Kepanjenkidul. Based on the results of observations and interviews, the obstacles faced by this MSMEs are the lack of business identity branding such as logos that look monotonous, unattractive, and old school. From these obstacles, group 23 helped rebrand Mbah Bendo Koi Farm's logo, apart from that we also helped create social media accounts and their content in the hope of attracting new potential customers and expanding their market in all regions in Indonesia.